Audiovisual tour of the Campsa - Guide: evolutionary analysis of a historical publication (1996 -2008) - de Castro Leal, Leticia; Rivas Sánchez, Iciar; Ruano Losa, Laura (Cuadernos de Documentación Multimedia, 2025)
This article is the second part of a documentary analysis of the television advertising campaigns for the Guía Campsa, following the study “Recorrido audiovisual de la Guía Campsa: análisis evolutivo de una publicación histórica (1988 -1995)”.The main objective is to examine the evolution of these campaigns during the period 1996–2008, a stage marked by the prominence of figures from Spanish cinema and television, replacing the literary prescriber who had featured in the earlier phase. Through documentary analysis and detailed timing of the television spots, the study explores two distinct periods: 1997–2003, during the peak of Spanish cinema, and 2004–2008, coinciding with the rise of national television fiction. The article concludes in 2008, the year prior to the rebranding of Guía Campsa as Guía Repsol, which will be addressed in a third installment.
Keywords: Hydrocarbon; CAMPSA Guide; REPSOL Guide; Advertising; Advertisements